Estimulación cognitiva para mejorar las funciones ejecutivas en los niños de sexto grado paralelo a, de la unidad educativa Marieta de Veintimilla, periodo 2020-2021. - Paredes Camacho, Erik Alexander (2021)
The present work of Curricular Integration called: COGNITIVE STIMULATION TO IMPROVE EXECUTIVE FUNCTIONS IN CHILDREN OF SIXTH GRADE PARALLEL A, OF THE EDUCATIONAL UNIT MARIETA DE VEINTIMILLA, PERIOD 2020-2021; is established with the objective of: Implement a cognitive stimulation guide as an intervention strategy to improve executive functions in children in sixth grade parallel A of the Marieta de Veintimilla Educational Unit. The research is presented with a quantitative approach of descriptive type, quasi-experimental and cross-sectional design; based on the scientific, deductive, analytical and synthetic methods; a survey was applied as a technique, which was applied to three teachers of the institution; and the Neuropsychological Evaluation Battery of Executive Functions in Children (ENFEN) to a sample of ten students. The results of the survey applied to the teachers show that the great majority of them do apply cognitive stimulation activities; however, specifically for the executive function of attention and concentration, 66.66% do not apply and 33. 33% do; in relation to the evaluation of the executive functions applied to the sample of children investigated (pretest), in the fluency test that evaluates the executive function of expressive/comprehensive language: 30% are at a very low level, 20% are at a low level, 30% at a medium level, 10% at a medium-high level, and finally 10% at a high level; while in the executive function of verbal memory, the following results are presented: 10% Low, 30% Medium low, 30% Medium, 10% Medium high and finally 20% in High level; in relation to the Interference test that evaluates the executive function of attention and concentration, these are in levels: 20% Very low, 20% Low and finally 60% Medium level; after the execution of the proposal; and the respective application of the (post - test) in the executive function expressive/comprehensive language, the following results were obtained: 10% Low, 10% Medium low, 30% Medium, 30% High, and 20% Very high, likewise, from the evaluation of the executive function: Verbal memory, the following results and levels are 5 expressed: 10% Medium low, 20% Medium, 50% Medium high, 10% High and 10% Very high; finally from the executive function; attention and concentration 10% Low, 40% Medium and finally 50% Medium high. Therefore, it is concluded that the intervention proposal based on cognitive stimulation through the practical exercises that were executed, improved the executive functions evaluated in the children, which can be evidenced in the results of the pretest and post-test, for this reason it is recommended to the director of the Educational Unit "Marieta de Veintimilla" and to the students of the psychopedagogical career to consider the intervention proposal, which can be executed in the educational establishment, and serve as a practical basis for future research of university students.